Magnetic and processability studies of nitrile rubber vulcanisates containing barium ferrite and carbon black - Soloman, M. A.; Kurian, P.; Anantharaman, Maliemadom R.; Joy, Pattayil Alias (Indian Journal of Chemical Technology, 2005)
Fine particles of barium ferrite (BaFe12O19) belonging to the M-type hexagonal ferrites were prepared by the conventional ceramic techniques. They were incorporated into a nitrile rubber matrix according to a specific recipe for various loadings to produce rubber ferrite composites (RFC)The percolation threshold is not reached for a maximum loading of 130 phr (parts per hundred rubber). Here in this paper, the magnetic properties and processability of the nitrile rubber based RFCs containing barium ferrite (BaF) and HAF carbon black is reported. The magnetic properties of the ceramic ferrite and these rubber ferrite composites were evaluated and it was found that the coercivity values of RFCs were less than that of the ceramic BaF, but remained constant with the loading of both the ferrite filler and carbon black. However, other properties like saturation magnetization and magnetic remanence increased with the loading of ferrite filler.
Keywords: barium ferrite; carbon black; Magnetic materials; nitrile rubber; rubber ferrite composites

Magnetic properties of nanosized ferrite powders synthesized by microwave-hydrothermal method - Khollam, Y. B.; Dhage, S. R.; Verma, S.; Potdar, H. S.; Deshpande, S. B.; Joy, Pattayil Alias; Date, Sadgopal K. (Ninth International Conference on Ferrites (ICF-9), 2005)
Nanosized powders of Fe3O4 and MgFe2O4 are synthesized by microwave-hydrothermal (MH) method. The ferrite powders thus obtained are characterized by powder X-ray diffraction, Mossbauer spectroscopy, scanning and transmission electron microscopies, vibrating sample magnetometer and AC magnetic susceptibility studies. Stoichiometric, nanosized (similar to 34 nm) Fe3O4 particles, having cubic symmetry with a(0) approximate to 8.39 angstrom, are obtained when molar ratio of Fe/NaOH used for the synthesis is 0.133. On the other hand, non-stoichiometric Fe3O4 is obtained when Fe/NaOH molar ratio is increased to 0.4. Though the powder XRD patterns of both stoichiometric and non-stoichiometric Fe3O4 are identical, Mossbauer spectroscopic studies showed different features in terms of asymmetry, intensity, isomer shift, etc. Saturation magnetization, M-s = 70 emu/g and coercivity, H-c = 178 Oe, at room temperature, are obtained for stoichiometric Fe3O4 powders. In the case of MgFe2O4, spherical, nanosized (similar to 3 nm) powders with cubic symmetry (a(0) approximate to 8.30 angstrom) and having very narrow size distribution are obtained under the MH conditions. The temperature and field dependent magnetic measurements on MgFe2O4 powders confirmed the existence of superparamagnetic state in this material with a superparamagnetic blocking temperature of 38 K below which typical magnetic hysteresis behaviour is observed.

Magnetic properties of the self-doped lanthanum manganites La1-xMnO3 - Sankar, C. R.; Joy, Pattayil Alias (Physical Review B, 2005)
The magnetic properties of different compositions in the self-doped lanthanum manganites, La1-xMnO3, have been studied by ac susceptibility and dc magnetization measurements in the temperature range 10-300 K. All compositions with x < 0.125 show an anomalous decrease in the ac susceptibility and zero field cooled (ZFC) dc magnetization at low temperatures, below the ferromagnetic ordering temperature. The temperature below which this anomalous behavior is observed, T-a, varies with the degree of La vacancy in the series where the Mn4+ concentration decreases with increasing x. Moreover, T-a varies with the Mn4+ content for a given composition. However, in both cases, this temperature levels off when the concentration of Mn4+ is above 23%. The magnetic-transition-like feature broadens and shifts to further lower temperatures with increasing magnetic fields and vanishes when measured above a certain field. A small but drastic increase in the coercivity is observed below T-a. There is a direct correlation between the shapes of the curves of the inverse of the coercivity as a function of temperature and ac susceptibility, indicating the influence of magnetic anisotropy on the characteristics of the ac susceptibility and zero field cooled magnetization curves of the self-doped compounds. The direct correlation between the changes in the coercivity and ac susceptibility as well as ZFC magnetization when measured at low magnetic fields give evidence to the role of domain wall pinning effects, which varies with the degree of self-doping or Mn4+ concentration.

Modifications in magnetic anisotropy of M-type strontium hexaferrite crystals by swift heavy ion irradiation - Kaur, Balwinder; Bhat, Monita; Licci, F.; Kumar, Ravi; Kulkarni, S. D.; Joy, Pattayil Alias; Bamzai, K. K.; Kotru, P. N. (Journal of Magnetism and Magnetic Materials, 2006)
Using vibrating sample magnetometery (VSM) 50 MeV Li(3+) ion irradiation effects on magnetic properties of single crystals of SrGa(x)In(y)Fe(12-(x+y))O(19) (where x = 0, 5, 7, 9; y = 0, 0.8, 1.3, 1.0), are reported. The substitution of Ga and In in strontium hexaferrite crystals decreases the value of magnetization sharply, which is attributed to shifting of collinear magnetic order to a non-collinear one. Reduction of magnetization is also explained to be as a result of the occupation of the crystallographic sites of Fe(3+) by Ga(3+) and In(3+). The Li(3+) ion irradiation decreases the value of magnetization, irrespective of whether the crystals are Ga-In substituted or unsubstituted crystals of SrFe(12)O(19). The result is interpreted in terms of the occurrence of a paramagnetic doublet in crystals replacing magnetic sextuplet as a result of irradiation. Substitution of Ga-In in Strontium hexaferrite decreases the value of anisotropy constant. Irradiation with Li(3+) ions increases the values of anisotropy field for both substituted as well as unsubstituted crystals. Substitution with Ga-In also decreases the Curie temperature (T(c)) but the irradiation with Li(3+) ions does not affect the curie temperature of either Ga-In substituted or pure SrFe(12)O(19) crystals. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: anisotropy field; Curie temperature; irradiation; Magnetic anisotropy; Magnetization

Multiutility sophorolipids as nanoparticle capping agents: synthesis of stable and water dispersible Co nanoparticles - Kasture, Manasi; Singh, Sanjay; Patel, Pitamber; Joy, Pattayil Alias; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (Langmuir, 2007)
Sophorolipids are a class of glycolipids that can be obtained from fatty acids by simply treating them with yeast cells (Candida bombicola, ATCC 22214) and glucose. In this letter, we demonstrate the application of sophorolipids obtained from oleic acid as a capping agent for Co nanoparticles. Upon capping the nanoparticle surface, the sugar moiety of these sophorolipids is exposed to the solvent environment, making the nanoparticles stable and water-redispersible.

Magnetic and Mossbauer spectroscopic studies of NiZn ferrite nanoparticles synthesized by a combustion method - Sreeja, V.; Vijayanand, S.; Deka, Sasanka; Joy, Pattayil Alias (Hyperfine Interactions, 2008)
The properties of nanocrystalline Ni(0.5)Zn(0.5)Fe(2)O(4) synthesized by an auto-combustion method have been investigated by magnetic measurements and Mossbauer spectroscopy. The as-synthesized single phase nanosized ferrite powder is annealed at different temperatures in the range 673-1,273 K to obtain nanoparticles of different sizes. The powders are characterized by powder X-ray diffraction, vibrating sample magnetometer, transmission electron microscopy and Mossbauer spectroscopy. The as-synthesized powder with average particle size of similar to 9 nm is superparamagnetic. Magnetic transition temperature increases up to 665 K for the nanosized powder as compared to the transition temperature of 548 K for the bulk ferrite. This has been confirmed as due to the abnormal cation distribution, as evidenced from room temperature Mossbauer spectroscopic studies.
Keywords: Ferrite; magnetic properties; Mossbauer spectroscopy; Nanoparticles

Magnetic characteristics of nanocrystalline multiferroic BiFeO3 at low temperatures - Vijayanand, S.; Mahajan, Mangesh B.; Potdar, H. S.; Joy, Pattayil Alias (Physical Review B, 2009)
The magnetic characteristics of nanocrystalline BiFeO3 with average crystallite sizes of similar to 50 and similar to 100 nm are evaluated by studying the temperature and field dependence of magnetization at low temperatures. Different properties such as magnetization, coercivity, and remanence show evidence for changes in the magnetic properties associated with the phase transitions at low temperatures, reported from Raman studies. Detailed field-cooled and zero-field-cooled magnetization measurements show that the likely origin of the changes in the magnetic characteristics is from the changes in the domain structure.
Keywords: bismuth compounds; coercive force; crystallites; magnetic domains; magnetic transitions; Multiferroics; Nanostructured materials; Raman spectra; remanence

Multiferroic behavior of gd based manganite - Sagar, S.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Ferroelectrics, 2009)
Here we report the multiferroic nature of charge ordered manganite Gd0.5Sr0.5MnO3 for the first time. The temperature variation of dielectric constant shows broad relaxor type ferroelectric transition at around 210K and magnetization measurements shows weak ferromagnetism at 50K. The dielectric peak is very close to charge ordering temperature which is an evidence of the link between electronic state and increase of dielectric response. Butterfly variation of capacitance with voltage confirms ferroelectric nature of the sample at room temperature.
Keywords: dielectric constant; manganite; Multiferroic

On the magnetic and dielectric properties of nickel-neoprene nanoconaposites - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Materials Chemistry and Physics, 2010)
Nickel nanocomposites were prepared by incorporating nickel nanoparticles in a neoprene matrix according to a specific recipe for various loadings of nickel particles. The dielectric properties of these composites were evaluated for different frequencies ranging from 100 kHz to 8 MHz at different temperatures from 30 degrees C to 120 degrees C. The dielectric permittivity increases with increase of nickel concentration. Increase in temperature enhances the permittivity initially, till 40 degrees C and thereafter the permittivity decreases. The dielectric loss exhibits relaxation peaks and the peaks shift to lower frequencies with increase in volume fraction of the nickel nanoparticles in the matrix. The evaluation of magnetic and dielectric properties of these composites suggests that the dielectric permittivity can be tailored by an appropriate loading of the filler using semi-empirical equations and the magnetic properties vary according to simple mixture equations. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Composite materials; dielectric properties; Elastomers; magnetic properties

On the magnetic, mechanical and rheological properties of rubber-nickel nanocomposites - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Polymer Bulletin, 2010)
Rubber-nickel nanocomposites were synthesized by incorporating freshly prepared nanometric nickel particles in two different matrices namely natural rubber and neoprene rubber according to specific recipes for various loadings of nano nickel and the cure characteristics of these composites were evaluated. The maximum torque values register an increase with the increase in loading of nickel in both composites and this is attributed to the non-interacting nature of nickel nanoparticles with rubber matrices. The cure time of natural rubber composites decreases with increase in the content of nickel, and in neoprene rubber cure, time increases with increase in filler content. In natural rubber, the curing reaction seems to be activated by the presence of nickel particles. The magnetization studies of the composites reveal that the magnetic properties of nickel are retained in the composite samples. The elastic modulus of natural rubber and neoprene rubber are largely improved by the incorporation of nickel particles.
Keywords: Cure characteristics; Elastic modulus; magnetic properties; Nanocomposites

Magnetic and electric responsive hydrogel-magnetic nanocomposites for drug-delivery application - Reddy, N. Narayana; Mohan, Y. Murali; Varaprasad, K.; Ravindra, S.; Joy, Pattayil Alias; Raju, K. Mohana (Journal of Applied Polymer Science, 2011)
Magnetic and electrically responsive hydrogel networks were developed for drug-delivery applications. The hydrogel matrices were synthesized by the polymerization of acrylamide monomer in the presence of carboxymethylcellulose (CMC) or methylcellulose (MC) with N,N-methylenebisacrylamide, a crosslinker with the redox initiating system ammonium persulfate/tetramethylethylenediamine. The magnetic nanoparticles were generated throughout these hydrogel matrices by an in situ method by the incorporation of iron ions and their subsequent reduction with ammonia. A series of hydrogel-magnetic nanocomposites (HGMNCs) were developed with various CMC and MC compositions. The synthesized HGMNCs were characterized with spectral (Fourier transform infrared and ultraviolet-visible spectroscopy), X-ray diffraction, thermal, and microscopy methods. These HGMNCs contained iron oxide (Fe3O4) nanoparticles with an average particle size of about 22 nm, as observed by transmission electron microscopy. The dielectrical properties of the pure hydrogel (HG); the hydrogel loaded with iron ions, or the hydrogel iron-ion composite (HGIC); and the HGMNCs were measured. These results suggest that HGMNCs exhibited higher dielectric constants compared to HG and HGICs. The curcumin loading and release characteristics were also measured for HG, HGIC, and HGMNC systems. These data revealed that there was a sustained release of curcumin from HGMNCs because of the presence of magnetic nanoparticles in the hydrogel networks. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 1364-1375, 2011
Keywords: hydrogels; magnetic polymers; Nanocomposites; nanoparticle; nanotechnology

Magnetic and magnetoelastic properties of Zn-doped cobalt-ferrites-CoFe2-xZnxO4 (x=0, 0.1, 0.2, and 0.3) - Somaiah, Nalla; Jayaraman, Tanjore V.; Joy, Pattayil Alias; Das, Dibakar (Journal of Magnetism and Magnetic Materials, 2012)
Cobalt-ferrite (CoFe2O4) based materials are suitable candidates for magnetomechanical sensor applications owing to a strong sensitivity of their magnetostriction to an applied magnetic field. Zn-doped cobalt-ferrites, with nominal compositions CoFe2-xZnxO4 (x=0-0.3), were synthesized by auto-combustion technique using Co-, Fe-, and Zn-nitrate as precursors. X-ray spectra analysis and Transmission electron microscopy studies revealed that the as-prepared powders were comprised of nano-crystalline (similar to 25-30 nm) cubic-spinel phase with irregularly-shaped grains morphology along with minor impurity phases. Calcination (800 degrees C for 3 h) of the precursor followed by sintering (1300 degrees C for 12 h) resulted in a single phase cubic-spinel structure with average grain size similar to 2-4 mu m, as revealed from scanning electron micrographs. The magnitude of coercive field decreases from similar to 540 Oe for x=0 to 105 Oe for x=0.30. Saturation magnetization initially increases and peaks to similar to 87 emu/g for x=0.2 and then decreases. The peak value of magnetostriction monotonically decreases with increasing Zn content in the range 0.0-0.3; however the piezomagnetic coefficient (d lambda/dH) reaches a maximum value of 105 x 10(-9) Oe-1 for x=0.1. The observed variation in piezomagnetic coefficient in the Zn substituted cobalt ferrite is related to the reduced anisotropy of the system. The Zn-doped cobalt-ferrite (x=0.1) having high strain derivative could be a potential material for stress sensor application. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Cobalt-ferrite; Magnetic-properties; Magnetostriction

Magnetism in disordered carbon as a function of the extent of graphitization - Raj, K. Govind; Joy, Pattayil Alias (Solid State Communications, 2014)
Magnetic properties of disordered carbon have been investigated as a function of the extent of graphitization. It is found that the magnetization of the disordered carbon decreases with increasing degree of graphitization. Treatment with acid modifies the magnetic characteristics considerably and the original magnetic characteristics are retained upon further heat treatment. The results show that the intrinsic magnetic behavior of the disordered carbon depends on the microstructure and that the edge states play a critical role in deciding the magnetic interactions in the amorphous carbon system. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Amorphous carbon; disordered carbon; Graphitization; magnetic properties

Magnetoelastic properties of terbium substituted cobalt ferrite - Bhame, Shekhar D.; Joy, Pattayil Alias (Chemical Physics Letters, 2017)
The magnetic properties of terbium substituted cobalt ferrites CoFe(2-x)TbxO(4) (x = 0, 0.05, 0.1, 0.15 and 0.2) prepared by conventional solid state method are studied. The coercivity showed marked increase up to x = 0.1 and saturation magnetization decreased with increasing terbium content. Magnetostriction measurements did not show much decrease in the maximum value of strain but significant increase in the slope of magnetostriction was observed for x = 0.15 with moderate magnetostriction of around 144 ppm. The observed magnetic and magnetostrictive properties can be explained on the basis of structural and microstructural changes arising because of terbium substitution. (C) 2017 Elsevier B.V. All rights reserved.

MgB2/NaNO2-PVA free-standing polymer composite film as a green firework: a step towards environmental sustainability - Jeyavani, Vijayakrishnan; Kumar, Rajendra; Joy, Pattayil Alias; Mukherjee, Shatabdi Porel (Bulletin of Materials Science, 2022)
We have demonstrated a simple fabrication methodology of free-standing polymer composite film firework that sparkles, provides colour display and moderate sound, yet is less polluting. The polymer composite film fireworks are composed of magnesium boride (MgB2), sodium nitrite (NaNO2) and poly(vinyl alcohol) (PVA). This study also suggested that a flammable, explosive powder composition can be made of two very common inorganic precursors, mainly NaNO2 and MgB2 . This is the first report demonstrating composite film fireworks with new flammable composition using metal boride as a primary precursor, which can also be used in conventional fireworks fabrication, replacing the traditional fuel, mainly gunpowder. The film fireworks were free from charcoal, sulphur, metal powder and paper. Therefore, they substantially lower the odour and COx, NOx, emissions and minimize the substantial trash generated when burned. Most importantly, film firework's minimum ignition temperature and exothermic decomposition temperature are much higher than the ambient temperature; hence are safe to handle.
Keywords: Firework; free-standing film; magnesium boride (MgB2); poly(vinyl alcohol) (PVA); sodium nitrite (NaNO2)